Isolation and identification of parasites from the soil in public park at Kuala Pilah / Nurlisa Diyana Elyas Yeow - Elyas Yeow, Nurlisa Diyana
One of the main routes for the transmission of many pathogen parasites was through the eggs present in human and animal faeces, therefore contaminated soil in areas where the hygiene is deprived. This research was performed to isolate pathogen parasites from a public playground in Kuala Pilah and to identify the parasites that can cause pathogenic parasite infections in human. For this research, two of the concentration methods have been used to isolate the parasite from soil of five chosen public parks around Kuala Pilah, which is, the Floatation method and Sedimentation Method. The result from this research showed that 26 out of 50 sample have give positive result for presence of parasite with Strongyloides sp. shows the highest number of parasite compared to Trichinella sp. and Angiostrongylus sp. This research could be useful for further research of pathogen parasite in Kuala Pilah public park by using more confirmative method such as PCR.